Fase Transisi Infiltrasi pada Tegakan Mahoni dan Akasia di Hutan Pendidikan: Pendekatan Model Horton - Nurdin Dalya; Hadija; Asjulia Eboni; Wahyullah Eboni (Jurnal Eboni, 2026)
Infiltration is a critical hydrological process that controls water movement into the soil and influences runoff generation, groundwater recharge, and watershed stability in forest ecosystems. This study aimed to analyze the infiltration transition phase under mahogany and acacia stands using the Horton infiltration model in an educational forest area. Field observations were conducted under approximately 60-year-old stands consisting of three observation plots for each stand. Infiltration measurements were recorded for 30 minutes in each plot. The results showed that infiltration rates in both stands followed an exponential decline pattern consistent with the Horton model. However, distinct differences in infiltration transition behavior were identified between mahogany and acacia stands. Acacia stands exhibited a rapid infiltration decline and reached the transition phase faster, generally within the first 6–8 minutes, indicating a quicker shift toward quasi-steady infiltration conditions. In contrast, mahogany stands demonstrated a more gradual decline, with a longer infiltration persistence, during which the transition phase occurred around 10–15 minutes before approaching stable conditions. The findings suggest that mahogany stands exhibit greater hydrological resilience and higher temporary water storage capacity than acacia stands. In addition, infiltration variability among plots revealed substantial micro-site heterogeneity despite similar stand ages. These results emphasize the importance of stand characteristics in controlling temporal infiltration dynamics and hydrological functions in tropical plantation forests.